Body Centric Knowledge: Traditions of Performance and Pedagogy in Kathakali - Mundoli Narayanan
Most traditional Indian performance forms are characterised by distinct modes of embodied knowledge that increase in intensity with the degree of systematization present in their performative practices and also problematize the mind-body hierarchies that are inherent to most modern schemes of thought. The instance of Kathakali, the traditional performance form of Kerala, is taken to consider how a repetitive training regimen that inscribes in the young student a comprehensive language and aesthetic of performance is employed to establish a distinctive ‘body mind’ and a ‘body memory’ that almost entirely elide the participation or intervention of the ‘conscious mind’. There is also the inherent expectation that this formal embodied knowledge will come to be informally enriched in performance by a greater awareness of the aesthetic, emotive, thematic and other significant aspects of performance, as the student acquires life experience and matures both as a person and as a practitioner. Underlying this pedagogy is a certain relationship between the teacher and the student, characterised by the exercise of hierarchical power and violence from one side, and submissive compliance and deference from the other, which is at once both an extension and a recreation in an instructional setting of a set of social relations and certain paradigms of social power, class and patronage that are to do with the time in which the form evolved. The paper also examines the tensions that have developed in these pedagogic practices today in the context of modern institutions and the vastly different modalities of teacher/student subjectivities and relationships